Fanaber complex as the highest form of anti-spirituality (Literatures of the World: Poetics, Mentality and Spirituality, 2017)
The article studied the psychotypefanaberia whichwas clearly revealed in the works of Ukrainian literature, also the history of the formation of fanaberiawas studied, the peculiarities of the complex «fanaberia»,and its anti-spiritual nature were identified. The author noted that  one’s own conceit, and therefore contemptuous attitude to others, has a negative impact, primarily on the holder of these features. The formationof fanaberia development is reasoned to consist of serious shortcomings committed by parents in the upbringing of their children.
Keywords: psychotype; fanaberia; complex; anti-spiritual